2020
DOI: 10.3390/catal11010046
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Microwave-Assisted Copper-Catalyzed Cross-Coupling Reactions

Younis Baqi

Abstract: Cross-coupling reactions furnishing carbon–carbon (C–C) and carbon–heteroatom (C–X) bond is one of the most challenging tasks in organic syntheses. The early developed reaction protocols by Ullmann, Ullman–Goldberg, Cadiot–Chodkiewicz, Castro–Stephens, and Corey–House, utilizing elemental copper or its salts as catalyst have, for decades, attracted and inspired scientists. However, these reactions were suffering from the range of functional groups tolerated as well as severely restricted by the harsh reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 143 publications
(138 reference statements)
0
17
0
Order By: Relevance
“…Although a general screening of ligands for the above studies was not carried out, the popular N , N′ -dimethylethylenediamine (DMEDA) [ 7 , 8 , 9 , 10 ] was examined briefly to see how it competes with phen as a ligand for the Goldberg reaction of 2-bromopyridine and secondary amides. The usual loading for CuI/DMEDA reactions of this type is 1/2 with CuI at 5–10%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a general screening of ligands for the above studies was not carried out, the popular N , N′ -dimethylethylenediamine (DMEDA) [ 7 , 8 , 9 , 10 ] was examined briefly to see how it competes with phen as a ligand for the Goldberg reaction of 2-bromopyridine and secondary amides. The usual loading for CuI/DMEDA reactions of this type is 1/2 with CuI at 5–10%.…”
Section: Resultsmentioning
confidence: 99%
“…recent years using various aryl and heteroaryl halides [7][8][9][10], only a few examples have been reported that provide MAPA-related compounds from 2-halopyridines. Some examples are depicted below (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Cross-coupling reactions furnishing carbon-carbon (C-C) and carbon-heteroatom (C-X)bond is still one of the most challenging area in organic syntheses. Younis Baqi has reported [49] a comprehensive review on Recent Advances in Microwave-Assisted Copper-Catalyzed Cross-Coupling Reactions very recently. The microwave energy was also used in the synthesis of Ribonucleosides using natural phoshphate as catalyst in 2013 by Ouzebla et al [50].…”
Section: H Coupling Reactionsmentioning
confidence: 99%
“…These devices can accomodate several rotor types for parallel reactions in a vessel volume up to 100 mL. [30][31][32][33] Although the chemical literature provides a valuable number of reviews on copper-and nickel-catalyzed reactions, [34][35][36][37] this review article critically focuses the attention on the recent progress on copper-and nickel-catalyzed cross-coupling reactions using various metal catalysts under distinctive attributes of microwave heating reported during the last decade. It highlights as well on the more stable and sustainable metal catalysts used; the improvement and intensification of reaction selectivity are symbolizing the current challenges in order to reach to the well-established activity level of palladium catalysts.…”
Section: Introductionmentioning
confidence: 99%